Coupling ecosystem service value and ecological vulnerability for spatial zoning and adaptive pathways under future scenarios: a case study of Northern Shaanxi, China - Wang, Meng; Fu, Jianmei; Huang, Xin; Bai, Yu (Frontiers in Environmental Science, 2026)
IntroductionThe imbalance between ecosystem service supply and demand, combined with increasing ecological vulnerability, poses a significant challenge to the sustainable development of ecologically sensitive regions. Northern Shaanxi, a typical agro-pastoral zone in China with ecological fragility, is highly susceptible to severe soil erosion, desertification, and water scarcity. These stresses are intensified by intensive human activities and climate change. Therefore, it is necessary to systematically clarify the spatial differentiation of ecosystem service value (ESV) and vulnerability in this region, and to propose regionally tailored optimization and regulation strategies.MethodsThis study introduces a “classification–simulation–strategy alignment” analytical framework to examine the interaction between ESV and ecosystem vulnerability (EV). Using Northern Shaanxi as a case study, the spatiotemporal dynamics of ESV and EV are quantitatively analyzed from 2000 to 2020. According to the spatial coupling relationship between ESV and EV, the region is divided into four functional zones: Low ESV–Low EV (general utilization areas), High ESV–Low EV (ecological stability areas), Low ESV–High EV (key restoration areas), and High ESV–High EV (core protection areas). The PLUS model is applied to simulate various future development scenarios, assess the ecological responses across these zones, and propose targeted adaptive management strategies for Northern Shaanxi.ResultsThe results indicate that ESV is generally higher in the southeast and lower in the northwest, whereas EV declines from northwest to southeast. Under future scenarios, key restoration areas and core protection areas show elevated ecological sensitivity and should be prioritized in governance efforts. Scenario simulations support the development of region-specific management strategies and contribute to a systematic governance pathway based on “classification–simulation–strategy alignment” tailored to the challenges of Northern Shaanxi.DiscussionThis study advances understanding of the coordinated evolution of ESV and EV, providing both theoretical and practical foundations for precise zoning management and adaptive ecological governance in Northern Shaanxi. The findings also offer valuable insights for other ecologically sensitive regions with similar characteristics.